Evaluation of eukaryotic cultured cells as a model to study extracellular DNA - Peters, Dimetrie Leslie (North-West University, 2011)
The diagnostic value of extracellular occurring DNA (eoDNA) is limited by our lack of understanding its biological function. eoDNA exists in a number of forms, namely vesicle bound DNA, histone/DNA complexes or nucleosomes and virtosomes. These forms of DNA can also be categorized under the terms circulating DNA, cell free DNA, free DNA and extracellular DNA. The DNA can be released by means of form-specific mechanisms and seem to be governed by cell cycle phases and apoptosis. Active release is supported by evidence of energy dependant release mechanisms and various immunological- and messenger functions. Sequencing has shown that eoDNA sequences present in the nucleome reflects traits and distribution of genome sequences and are regulated by ways of release and/or clearance. eoDNA enables the horizontal transfer of gene sequences from one cell to another, over various distances. The ability of eoDNA to partake in horizontal gene transfer makes it an important facet in the field of epigenetic variation. Clinical implementation of eoDNA diagnostics requires that all of the subgroups of eoDNA be properly investigated. It is suggested that eoDNA is the result of the metabolic fraction of DNA that is released by the cell. Various observations indicate that eoDNA may also be incorporated into the genome of a cell, from where it may affect cell function. Therefore horizontal gene transfer in higher organisms is a real possibility. In this study, variations and increases in eoDNA levels over time correlate with stressors that are subjected to 143B human osteosarcoma cells. It seems viable to assume that a stressor is met by a change in the molecular machinery of a cell, required to neutralise the onset of metabolic instability. This may be done by amplification of necessary cistrons, producing metabolic DNA, that may then be observed after its release as eoDNA. The presence of hydrolysing enzymes gives an updated real time picture of the state of eoDNA. The eogenics hypothesis emanating from this study, suggests that amplification and horizontal transfer of cistrons affect tissue and organ function over long periods of time, in order for an organism to evolve one or more a specialized genomes.
Thesis (M.Sc. (Biochemistry))--North-West University, Potchefstroom Campus, 2011.
Keywords: Circulating; Extracellular; Nucleic Acids; Deoxyribonucleic acid (DNA); Horizontal Gene Transfer; Virtosome; Blood Nucleome